Multiple cutaneous metastasis of sacral chordoma, mimicking neurofibromas clinically - Narang, Neha Chopra; Narang, Salil; Diwaker, Preeti (Annals of Pathology and Laboratory Medicine, 2018)
Chordoma is a rare primary bone tumor of notochordal origin, constituting 1-4% of malignant primary bone tumors. Chordomas are slow growing tumors and show aggressive local extension, multiple recurrences and metastasis. Cutaneous metastasis of chordoma is very rare. We report a case of a 61-year-old man presenting with multiple cutaneous metastasis of primary sacral chordoma. DOI:10.21276/APALM.1753